HOW TO REMOVE ANXIETY OF MULTILINGUAL CLASSROOMS? - Aneela Bushra Maqbool (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
The purpose of the paper is to reveal a key issue of multilingual classroom i.e. anxiety. When the teacher is mono-or bi-lingual and learners are multilingual then anxiety level of students is very high which creates threatened, de-motivated, and hold-back attitude among students for learning. As a result, such multilingual classroom is nothing more than a prison for learners which blatantly impairs learning and hampers open communication between teacher and student, who belong to diverse lingual background. Therefore, the paper suggests a strategy acronym as OBWMC (Off and on throwing Basic Words in Multilingual Classrooms). The strategy invites instructor to learn some basic 20-25 words of the learners' mother tongue. In a multilingual classroom mere knowing 20-25 words of students' mother tongue can infuse interest among learners towards language learning, lowers the affectivefilter and bolsters learner's self-esteem. Moreover, it also increases respect for other languages and dispel monotony of monolingual classrooms.